Centralised Incubator Control System - Mtunzi, B.; Chamisa, M.; Madumbu, Z.; Gonye, N. R.; Nhenga-Mugarisanwa, F. (My University, 2016)
This paper presents an infant incubator system that protects and helps incubate a premature infant while in hospital. The device is economical, robust, and uses easily replaceable parts. It consists of a control mechanism that makes use of fans, a humidifier and a home heater rod to provide heat. The temperature and humidity were automatically controlled and maintained by a microcontroller. The incubator had a base designed to automatically weigh and log the infant’s weight. A Visual Studio interface was used to provide incubator chamber data and to evaluate the performance of the design. The system could weigh the weight of the infant as well as control the chamber temperature at 36.5°C and humidity at 40%. The system was able to maintain these conditions within a period of 5 seconds